Dually folate/CD44 receptor-targeted self-assembled hyaluronic acid nanoparticles for dual-drug delivery and combination cancer therapy. Issue 33 (3rd August 2017) - Song, Liang; Pan, Zhou; Zhang, Huabing; Li, Yanxiu; Zhang, Yinying; Lin, Jinyan; Su, Guanghao; Ye, Shefang; Xie, Liya; Li, Yang; Hou, Zhenqing
Abstract : Self-assembled methotrexate-hyaluronic acid-octadecylamine nanoparticles loaded with curcumin have dual-targeting and combinational anticancer effect to folate and CD44 receptors overexpressed cancer cells. Abstract : Nanoparticles (NPs) functionalized with targeting ligands have shown promise, but are still limited by their nonspecific uptake by certain healthy tissues and cells that express low or even comparable levels of receptors. To increase their accumulation at tumor sites while decreasing the unintended toxicity, a possible solution is the involvement of two separate tumor-specific ligands in the localization. In this study, a dual tumor-targeting drug-loaded NP system was self-assembled by the amphiphilic conjugate of methotrexate–hyaluronic acid–octadecylamine (MTX–HA–OCA) with curcumin (CUR) encapsulated within the hydrophobic core (designated as MTX–HA–OCA/CUR NPs). The advantages of this nanosystem are that the anticancer drug MTX can be utilized as a tumor-targeting ligand toward folate receptors due to its structural similarity to folic acid (FA), and HA can serve as another tumor-targeting ligand toward CD44 receptors. The MTX–HA–OCA/CUR NPs are ∼70 nm in diameter and have sustained/controlled drug release behavior. An in vitro cellular uptake and competition inhibition study exhibited that MTX–HA–OCA/CUR NPs could significantly enhance the internalization efficiency in HeLa cells via folate/CD44 receptor-mediated endocytosis as compared to HA–OCA/CUR NPs. More importantly, the in vitro cytotoxicity of MTX–HA–OCA/CUR NPs was significantly enhanced as compared to those of the HA–OCA/CUR NPs, both free drugs, and individual free drug. Furthermore, the real-time in vivo and ex vivo fluorescence imaging of HeLa tumor-bearing mice showed that MTX–HA–OCA/CUR NPs could more efficiently enhance their accumulation and improve the penetration at the tumor site as compared to HA–OCA/CUR NPs. Therefore, these dually folate/CD44 receptor-targeted self-assembled HA NPs for the co-delivery of both anticancer drugs might provide a promising strategy for dual-targeted combination cancer therapy.